2008
DOI: 10.1038/mp.2008.31
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action of mood stabilizers: is the arachidonic acid cascade a common target?

Abstract: Bipolar disorder is a major medical, social and economic burden worldwide. However, the mechanisms of action of effective antibipolar disorder drugs remain elusive. In this paper, we review studies using a neuropharmacological approach in unanesthetized rats, combined with kinetic, biochemical and molecular biology techniques, showing that chronic administration of three Food and Drug Administration-approved mood stabilizers (lithium, valproate and carbamazepine) at therapeutically relevant doses, selectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 177 publications
(180 reference statements)
2
89
2
1
Order By: Relevance
“…These effects are approximately opposite of what was observed with the low versus high n-3 PUFA diets in previous studies where low n-3 PUFA leads to conservation of DHA but not ARA ( 10,11 ). Recently, the Nurses' Health Study reported that an elevated intake of LA was associated with an increased risk of developing major depression ( 50 ), and preclinical studies suggest that drugs used to manage bipolar disorder decrease brain arachidonic acid metabolism ( 51,52 ). While much interest in dietary LA levels have focused around coronary heart disease risk, understanding how dietary n-6 PUFAs regulate the metabolism of ARA and DHA in the brain may also be important for determining dietary requirements.…”
Section: Resultscontrasting
confidence: 38%
“…These effects are approximately opposite of what was observed with the low versus high n-3 PUFA diets in previous studies where low n-3 PUFA leads to conservation of DHA but not ARA ( 10,11 ). Recently, the Nurses' Health Study reported that an elevated intake of LA was associated with an increased risk of developing major depression ( 50 ), and preclinical studies suggest that drugs used to manage bipolar disorder decrease brain arachidonic acid metabolism ( 51,52 ). While much interest in dietary LA levels have focused around coronary heart disease risk, understanding how dietary n-6 PUFAs regulate the metabolism of ARA and DHA in the brain may also be important for determining dietary requirements.…”
Section: Resultscontrasting
confidence: 38%
“…[14][15][16][17][18][19] Moreover, a large body of data implies that inhibition of inflammation may contribute to the therapeutic effects of psychotropic drugs. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] However, it is important to emphasize that many studies reported opposite findings; namely, that psychotropic drugs also exhibit pro-inflammatory effects. 10,31,[38][39][40][41] Furthermore, the mechanism underlying the anti-inflammatory properties of psychotropic drugs is not fully understood and it is not known whether their influence on inflammation contributes to their therapeutic and toxic effects.…”
Section: Introductionmentioning
confidence: 99%
“…[56][57][58][59] Another inflammatory pathway that is frequently linked to the pathophysiology of neurological disorders is the cyclo-oxygenase (COX)-PGs cascade. 20,21 PGs such as PGE 2 not only have many important physiological functions, but also contribute to a number of pathological processes. [60][61][62][63] The biosynthesis of PGs involves the release of arachidonic acid (AA) from membrane phospholipids by phospholipase A 2 and its conversion to PGs by COX.…”
Section: Introductionmentioning
confidence: 99%
“…such as bipolar disorder, in which evidence points to a pathological upregulation of brain AA signaling ( 14 ).…”
mentioning
confidence: 99%